Students’ Character in Social Interaction at SDI-Qu Al Bahjah Boarding School (Journal of Primary Education, 2017)
The purpose of this research was to reveal the kinds of character that being developed in schools and social interaction. A qualitative case study design was employed in this study. The subjects of this study were the principle of the school, students' supervisor, and students. This research used interviews, observations, and documentary study. Interactive models of analysis was used to analyze the the data. The findings of this research are (1) characters that are being developed in SDI-Qu Al Bahjah Boarding School Cirebon are religious character, discipline, and autonomy; (2) Strategies that used to develop students' characters in the boarding school are habit development, modeling given by the principles and students' supervisors, and students' motivation building; (3) three interactions found in the boarding school namely interaction between murokibahas students 'supervisors and students, interaction between murokibahand SDI-Qu Al Bahjah, and interaction among students. Those three belong to associative interactions of social interaction that involves cooperation in developing students' character in SDI-Qu Al Bahjah Boarding School Cirebon.